2009
DOI: 10.1002/ps.1755
|View full text |Cite
|
Sign up to set email alerts
|

Potential dermal pesticide exposure affected by greenhouse spray application technique

Abstract: Novel spray application techniques using spray booms greatly decrease operator exposure because the operator is not walking directly into the spray cloud and the sprayed crop, and because of their higher capacity. Depending on the type of spray application, different parts of the body need to be protected most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 59 publications
4
62
1
1
Order By: Relevance
“…The same result was obtained in both growth stages: at senescence, PDE was 1099 mL (1.10 ) walking forwards and 153 mL (0.15 ) walking backwards (ratio 7.2), whereas the corresponding values at flowering were 337 (0.34 ) and 114 mL (0.11 ), respectively, (ratio 3.0). Similar results were obtained by Nuyttens et al [50] when testing several spray application techniques in pepper greenhouses: dermal operator exposure using a standard spray gun was reduced by a factor 7 when walking backwards. Similarly, Bjugstad and Torgrimsen [34] found that walking forwards using a knapsack sprayer on cucumber plants 2.0-2.2 m high gave a dermal exposure almost four times greater than that when working backwards.…”
Section: Tests On Tomato Plants: Effects Of Walking Direction and Plasupporting
confidence: 76%
“…The same result was obtained in both growth stages: at senescence, PDE was 1099 mL (1.10 ) walking forwards and 153 mL (0.15 ) walking backwards (ratio 7.2), whereas the corresponding values at flowering were 337 (0.34 ) and 114 mL (0.11 ), respectively, (ratio 3.0). Similar results were obtained by Nuyttens et al [50] when testing several spray application techniques in pepper greenhouses: dermal operator exposure using a standard spray gun was reduced by a factor 7 when walking backwards. Similarly, Bjugstad and Torgrimsen [34] found that walking forwards using a knapsack sprayer on cucumber plants 2.0-2.2 m high gave a dermal exposure almost four times greater than that when working backwards.…”
Section: Tests On Tomato Plants: Effects Of Walking Direction and Plasupporting
confidence: 76%
“…As detailed in the following subsection a low-pass filter attenuates this effect. et al, 2011), and health hazard for humans and the environment (Martinez et al, 2002;García & Gadea, 2004;Nuyttens et al, 2009). As an alternative to the spray guns, vehicles equipped with spraying systems with vertical spray booms that move through the crop rows give better spray distribution over the plant canopy and reduce the human risks.…”
Section: Spraying Systemmentioning
confidence: 99%
“…As an alternative to the spray guns, vehicles equipped with spraying systems with vertical spray booms that move through the crop rows give better spray distribution over the plant canopy and reduce the human risks. Nuyttens et al (2009) notes that for a constant spay volume a human-driven vehicle reduces 60-fold the potential dermal exposure in comparison to a standard spray gun. Furthermore, the potential dermal exposure varied from 19.7 mL h -1 for a vehicle to 460 mL h -1 for a spray lance.…”
Section: Spraying Systemmentioning
confidence: 99%
“… The spray quality generated by agricultural nozzles plays an important role in the application of plant protection products. The ideal nozzle-pressure combination should maximize spray efficiency by increasing deposition and transfer of a lethal dose to the target (Smith et al, 2000) while minimizing residues (Derksen et al, 2008) and off-target losses such as spray drift (Nuyttens et al, 2007a) and user exposure (Nuyttens et al, 2009a). The most important spray characteristics influencing the efficiency of the pesticide application process are the droplet sizes, the droplet velocities and directions, the volume distribution pattern, the spray sheet structure and length, the structure of individual droplets and the 3D spray dimensions.…”
mentioning
confidence: 99%